A two-dimensional numerical study of peristaltic contractions in obstructed ureter flows. Issue 1 (2nd January 2018) - Najafi, Z.; Schwartz, B. F.; Chandy, A. J.; Mahajan, A. M.
Abstract: The flow of urine from the kidneys to the bladder is accomplished via peristaltic contractions in the ureters. The peristalsis of urine through the ureter can sometimes be accompanied, more specifically, obstructed to a certain degree, by entities such as kidney stones. In this paper, 2D axisymmetric computational fluid dynamics simulations are carried out using the commercial code ANSYS FLUENT, to model the peristaltic movement of the ureter with and without stone. The peristaltic movement was assumed to be a sinusoidal wave on the boundary of the ureter with a specific physiological velocity. While the first part of the study considers flow in the ureter with prescribed peristaltic contractions in absence of any obstruction, the second part compares the effect of varying obstructions (0, 5, 15, and 35%) in terms of spherical stones of different sizes. Pressure contours, velocity vectors, and profiles of pressure gradient magnitudes and wall shear stresses are presented along one bolus of the ureter, during contraction and expansion of the ureteral wall, in order to understand backflow, trapping and reflux phenomena, as well as monitor the health of the ureteral wall in the presence of any obstruction. The 35% ureteral obstruction case resulted in a significant backflow at the inlet in comparison to the other cases, and also a wall shear stress that was up to 20x larger than the case without any obstruction.